Direct Growth of Graphene on Silicon by Metal-Free Chemical Vapor Deposition - Tai, Lixuan; Zhu, Daming; Liu, Xing; Yang, Tieying; Wang, Lei; Wang, Rui; Jiang, Sheng; Chen, Zhenhua; Xu, Zhongmin; Li, Xiaolong (Nano-Micro Letters, 2017)
The metal-free synthesis of graphene on single-crystal silicon substrates, the most common commercial semiconductor, is of paramount significance for many technological applications. In this work, we report the growth of graphene directly on an upside-down placed, single-crystal silicon substrate using metal-free, ambient-pressure chemical vapor deposition. By controlling the growth temperature, in-plane propagation, edge-propagation, and core-propagation, the process of graphene growth on silicon can be identified. This process produces atomically flat monolayer or bilayer graphene domains, concave bilayer graphene domains, and bulging few-layer graphene domains. This work would be a significant step toward the synthesis of large-area and layer-controlled, high-quality graphene on single-crystal silicon substrates. Highlights: 1 Graphene was successfully grown on single-crystal silicon substrates using metal-free, ambient-pressure chemical vapor deposition. 2 Atomically flat monolayer or bilayer graphene domains, concave bilayer graphene domains, and bulging few-layer graphene domains can be produced by controlling the growth temperature. 3 In-plane propagation, edge-propagation, and core-propagation processes are proposed to evaluate the sequentially changing graphene domains.